The replacement of payroll tax by a tax on revenues: A study of sectorial impacts on the Brazilian economy - Wilton Bernardino da Silva; Nelson Leit\~ao Paes; Raydonal Ospina (EconomiA, 2015)
A topic of current research in discussion about the Brazilian economy is the exemption from payroll taxes, which aims to stimulate competitiveness of the firms, boosting economic growth. This topic was introduced in Brazil by new laws that proposed replacing the payroll tax with a new tax on revenues. The payroll tax rate of 20% was replaced by a tax rate of 1% or 2% on revenue. This change has been applied primarily in labor-intensive economic sectors. In this paper, a neoclassical model was used to evaluate some sectoral impacts of these tax changes. The results show positive effects of this reform, among them, the increase in aggregate consumption and capital stock. Employment also grows in the labor-intensive sector. However, under a government revenue neutral scenario, these effects are almost completely lost, which shows some evidence about the low efficiency of these reforms. – – Um tema em recente no âmbito da economia brasileira é a desoneraç\~ao da folha de pagamentos, a qual objetiva estimular a competitividade das firmas, em direç\~ao ao crescimento econômico. Este tópico foi introduzido no Brasil por meio de medidas provisórias as quais propunham substituir a alíquota previdenciária patronal incidente sobre a folha de pagamentos por uma nova alíquota incidente sobre o faturamento. A alíquota patronal de 20% foi substituída por uma alíquota de 1% ou 2% sobre o faturamento. Esta mudança sendo feita primeiramente em setores econômicos intensivos em m\~ao de obra. Neste artigo, um modelo neoclássico foi utilizado para avaliar alguns impactos setoriais advindos dessas mudanças. Os resultados evidenciam efeitos positivos dessa reforma, entre eles, crescimento do consumo agregado, e estoque de capital. O emprego também cresce no setor intensivo em trabalho. Entretanto, sob um cenário neutro de arrecadaç\~ao, esses efeitos s\~ao praticamente nulos, o que mostra alguma evidência acerca da baixa eficiência dessas reformas.
Keywords: C61; C68; E62; 330; Neoclassical models; Tax reforms; Payroll tax exemption